Grupo EmpreZa, que corpo é esse?: sensações de uma experiência-terreiro - Marcassa, Mariana Pedrosa (2011)
There are a few general questions related to performance which interest this dissertation: How does the creation of a performance happen? When is it that the performance actually happens? What is the relation of the performance with time? What state does the body of the performer find itself in performing? Which are the sensations of this performatic state? In order to explore these questions, I focus on the experiences of the art collective I integrate, since its beginning, Grupo EmpreZa. In this context, other questions appear: what machination of lines assembles us as a group, making of us a body? Which are the sensations of this body? How are they involved in the expression of our works? And, how does this a body express itself? The central aspect of this dissertation thinks the way in which these questions have opened what I call Experiência-Terreiro. With this concept, and in what is a work in process, I have the intention of amplifying the debate on the creative processes in the field of performance studies